Meta-analysis of the effectiveness of exercise as an intervention for suicidal tendency in depressed patients - Wenli Wang; Hairong Liu; Qiangming Feng; Yuanming Peng; Yanran Si (Frontiers in Psychology)
BackgroundThe objective of this study is to systematically evaluate the effects of exercise interventions on depressive symptoms and suicidal tendencies in patients with depression, and to investigate the differential impacts of various exercise programs on alleviating depressive symptoms.MethodsComputerized searches were conducted in PubMed, The Cochrane Library, Embase, WOS, EBSCO, CNKI, Wanfang, and VIP databases from their inception to May 5, 2025. Randomized controlled trials assessing the effect of exercise interventions on suicidal tendencies in depressed patients were screened by two independent researchers. The PEDro scale assessed study quality, and GRADEPro evaluated evidence quality. ReMan 5.4.1 was used for Meta-analysis and publication bias test. Standardized mean difference, Odds Ratio, and 95% CI were used as effect statistics.ResultsA total of 5 papers (5 RCTs with 796 patients) were included in this study. The results showed that exercise reduced depressive symptoms (SMD = −0.99, 95% CI [−1.95, −0.03], p = 0.04). But did not prevent suicidal ideation (SMD = −1.49, 95% CI [−4.33, 1.35], p = 0.30) and incidents of suicidal ideation in depressed patients (OR = 0.79, 95% CI [0.08, 7.67], p = 0.84). Among these, the heterogeneity of outcomes for depression was high, with potential influences including patient age, frequency, duration, and period of exercise, leading to moderate quality of evidence. Subgroup analyses showed that exercise had a antidepressant effect in middle-aged patients (SMD = −0.60, 95% CI [−1.06, −0.14], p = 0.01) and was effective from with a period of <12 weeks (SMD = −0.76, 95% CI [−1.05, −0.47], p < 0.00001), duration >30 min (SMD = −0.89, 95% CI [−1.32, −0.45], p < 0.00001), and frequency ≥3 times/week (SMD = −0.60, 95% CI [−1.06, −0.14], p = 0.01) had the largest effect size.ConclusionPhysical exercise was associated with an improvement in depressive symptoms. In contrast, physical exercise did not show a statistically effect on reducing suicidal tendencies and suicide risk among patients. Through subgroup analysis, it was found that the most beneficial intervention for physical exercise to relieve depressive symptoms was ≥3 times/week, lasting >30 min over <12 weeks, and combining various forms of aerobic exercise. For suicidal tendencies, however, a dose–response relationship could not be established due to limited literature.Systematic review registrationPROSPERO, Identifier CRD42024568335.